PENGARUH GAYA KEPEMIMPINAN, MOTIVASI, LINGKUNGAN KERJA, DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN (Studi Kasus Pada Badan Penanggulangan Bencana Daerah Kota Batu) - Enita yuliasari; Nur Hidayati; a agus Priyono (E-JRM : Elektronik Jurnal Riset Manajemen, 2020)
ABSTRACKThis study was conducted to analyze the impact of leadership style, motivation, work environment, and discipline on employee performance at BPBD Kota Batu. The sample for this study was 50 employees of the Batu City BPBD. The method used in this study was multiple linear regression with key data analyzed using the SPSS For Windows application. Based on the results of the research and discussion in the previous chapter, the conclusions of the simultaneous tests show that different leadership styles, motivations, work environments, and work disciplines affect employee performance. I am. Partial test results show that leadership style, motivation, work environment, and discipline variables influence employee performance. Keywords: Leadership style variables, motivation, work environment, discipline and work performance of employees